2D Dynamic Heterogeneous Interface Coupling Endowing Extra Zn2+ Storage. (29th January 2023) - Xiao, Baoquan; Chen, Jie; Hu, Changfa; Mou, Lianshan; Yang, Wenjing; He, Wenhao; Lu, Zhibin; Peng, Shanglong; Huang, Juanjuan
Abstract: Aqueous zinc‐ion battery (AZIBs) is expected to be an ideal device for large‐scale energy storage for its high safety and low cost. However, it is still a challenge to achieve both high energy density and high stability. Herein, in situ liquid‐phase growth exfoliation is developed to obtain V5 O12 nanosheets, which is then combined with Ti3 C2 nanosheets to construct two‐dimensional heterostructure (2D HVO@Ti3 C2 ) with interfacial VOTi bonds. 2D HVO@Ti3 C2 exhibits a dynamic interface coupling during discharging/charging, accompanied by break/reconstruction of interfacial VOTi bonds. The dynamic interface coupling provides a reversible electron transfer channel and endows the inert Ti3 C2 with electrochemical activity in AZIBs, making it an additional electron acceptor and donor, and promoting the insertion of more Zn 2+ . Therefore, a capacity beyond the theoretical capacity of HVO is obtained for the HVO@Ti3 C2 . Additionally, the reversible 2D dynamic interface coupling can also effectively alleviate the structural damage during the cycling process. Then, the ultra‐high capacity (457.1 mAh g ‐1 at 0.2 A g ‐1, over 600 mAh g ‐1 based on the mass of HVO) and high stability (88.9% capacity retention after 1000 cycles at 5 A g ‐1 ) are achieved. This interface coupling mechanism provides an exciting strategy for the high energy density and high stability of AZIBs. Abstract : The HVO@Ti3 C2 heterostructure materials with a 2D dynamic heterogeneous interface coupling makes the Ti3 C2 a conversion from the irreversible phase transition to reversible electrochemical activity in AZIBs. This unique structural characteristic can also effectively alleviate the structural damage during the discharging/charging processes. Therefore, an additional capacity contribution and enhanced cycle stability are achieved.